Culture of lymphocytes with a medium of green coconut juice - Nur Anisah Nur Anisah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
The study was aimed at investigating whether there were any difference on lymphocyte growth in in vitro by using RPMI 1640 and green coconut juice as medium. Lymphocytes were collected from spleen and bone marrow of 8 weeks old albino rats (Rattus norvegicus). Rats were sacrificed, subsequently spleen and bone marrow were taken and prepared for single cell suspension. Cells were counted using vital dye (Tripan biru) at 5x106 cells/ml. Twenty petri dishes were used. Half of them were used for spleen and the rest for bone marrow cell culture. In every group of those cells, petri were divided into two groups. One group used RPMI 1640 and the other a green coconut juice. Every petri dish was filled with 2 ml of suspension in cell media. All of the petri dishes were incubated in the incubator at 37°C, 5% CO2 for seven days. After 48 hours and 72 hours culture cells were examined and the percentage of viable cells was counted. Analysis of the viable cells between lymphocyte culture and bone marrow cells using RPMI .1640 and a green coconut juice was compared using Student's t-test and Anava. The results showed the increase of proliferation of viable cells from lymphocyte culture and bone marrow culture in both media hours were observed an after 72. As conclusion there is no significant difference between the growth of lymphocyte and bone marrow using RPMI 1640 and a green coconut juice (p>0,05).Key words: lymphocytes - cell culture - coconut juice - spleen cells - bone marrow cells